Artropodofauna associada às copas de Acacia mearnsii, Enterolobium contortisiliquum, Eucalyptus dunnii e Dodonaea viscosa em áreas mineradas e não minerada no Rio Grande do Sul - Machado, Leonardo Mortari (2018)
The main objective of the present study was to describe the arthropod fauna associated with the upper stratum of the species Acacia mearnsii, Enterolobium contortisiliquum, Eucalyptus dunnii and Dodonaea viscosa in mined and non-mined areas in Rio Grande do Sul, characterizing, through ecological parameters, the level of recovery of each treatment. In parallel, we sought to correlate the abundance of arthropods associated with the canopy of these forest species with the main meteorological variables that influence insects. In order to reach the proposed objectives, the present study was conducted in the city of Candiota, Rio Grande do Sul, where “Companhia Riograndense de Mineração (CRM)” explores Brazil's largest open-pit coal reserve. Thus, in the area covered by the Candiota mine, five areas recovered after mining and a non-mined area were selected, thus composing the six treatments of this study. To facilitate results presentation and discussion, this study was organized in five chapters. In this way, chapter I presents the general aspects and literature review. Chapter II encompasses aspects related to arthropod fauna present in the canopy of trees in areas recovered after the mining activity. Among these, one of the two areas recovered with E. dunnii presented the best results, differing statistically from the other areas. In chapter III, the arthropod fauna was studied in a non-mined area and in an area recovered after the mining activity, both with A. mearnsii, with the recovered area presented ecological parameters equal to or higher than those observed in the non-mined area. In Chapter IV, the population fluctuation of Glycaspis brimblemcombei and its natural enemy Psyllaephagus bliteus was studied in an area recovered with E. dunnii planting, with both populations presenting an outbreak in the summer, with low population density in the other seasons and with the average air temperature (°C) exerting influence on both species. In chapter V was carried out the first record of Heteropsylla caldwelli for Brazil, as well as the population fluctuation of this specie in E. contortisiliquum in the state of Rio Grande do Sul.